The IMPROVING STUDENT ACTIVITIES AND LEARNING OUTCOMES THROUGH RECIPROCAL TEACHING STRATEGIES WITH AUDIOVISUAL MEDIA - Munawaroh, Binti (Department of Mathematics Education , University of Jember, 2021)
The research is about classroom action research in class XI MIPA 2 SMA Negeri 3 Bondowoso in the 2019/2020 school year. Data collection methods in this research are observation, documentation, and tests. The data obtained are student interest in learning, teacher activities and student learning activities during the learning process and learning outcomes in cycle I and cycle II. Student learning activity data obtained from observations. Student learning activities were analyzed descriptively. While the completeness of students' mathematics learning outcomes was obtained from the postest results. Classical student learning activities have increased in each activity indicator observed from cycle I to cycle II. This can be seen from students who do activity indicators, the percentage increases from cycle I and cycle II, from 73% to 93%. The increase in completeness of student learning outcomes occurred in each cycle, namely 31.5% in cycle I to 89.6% in cycle II. Based on the results above, it shows that the Reciprocal Teaching Strategy with Audiovisual Media can be used as an alternative to learning that can make students more active and can understand mathematical concepts in order to improve learning activities and student learning outcomes.